"Share and scare": Solving the communication dilemma of early adopters with a high need for uniqueness. Issue 1 (12th June 2014) - Moldovan, Sarit; Steinhart, Yael; Ofen, Shlomit
Abstract: Early adopters are considered essential to new product success due to their role in encouraging others to adopt. In this paper, we show that this may not always be true. Early adopters with a high need for uniqueness may experience a communication dilemma of whether or not to communicate about innovations they adopt. The dilemma derives from the clash between their need to flaunt the innovation they adopted and their desire to preserve their uniqueness by preventing imitation by others. We suggest that this dilemma might be resolved by a "share and scare" strategy, in which early adopters share information about their adoption with others yet scare them out of adopting it. In a series of four studies, we demonstrate early adopters' communication dilemma, the "share and scare" strategy, and three moderators that confirm our theory.